Characterization of old RHDV strains by complete genome sequencing identifies a novel genetic group. Issue 1 (December 2017) - Lopes, Ana; Silvério, Diogo; Magalhães, Maria; Areal, Helena; Alves, Paulo; Esteves, Pedro; Abrantes, Joana
Abstract Rabbit hemorrhagic disease (RHD) is a veterinary disease that affects the European rabbit and has a significant economic and ecological negative impact. In Portugal, rabbit hemorrhagic disease virus (RHDV) was reported in 1989 and still causes enzootic outbreaks. Several recombination events have been detected in RHDV strains, including in the first reported outbreak. Here we describe the occurrence of recombination in RHDV strains recovered from rabbit and Iberian hare samples collected in the mid-1990s in Portugal. Characterization of full genomic sequences revealed the existence of a single recombination breakpoint at the boundary of the non-structural and the structural encoding regions, further supporting the importance of this region as a recombination hotspot in lagoviruses. Phylogenetic analysis showed that in the structural region, the recombinant strains were similar to pathogenic G1 strains, but in the non-structural region they formed a new group that diverged 13% from known strains. No further reports of such group exist, but this recombination event was also detected in an Iberian hare that was associated with the earliest species jump in RHDV. Our results highlight the importance of the characterization of full genomes to disclose RHDV evolution and show that lagoviruses' diversity has been significantly undersampled.